Sulfur autotrophic denitrification filler for nitrogen wastewater treatment and preparation method thereof

By designing the chemical composition and microstructure of porous composite particles, the problem of interface passivation caused by calcium sulfate crystallization in the sulfur autotrophic denitrification process was solved, achieving long-term stable operation and efficient denitrification of the system, and reducing operating costs.

CN121044713AActive Publication Date: 2025-12-02DONGGUAN HUANJIE CHEM CO LTD

Patent Information

Application Number
CN202511285262.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-12-02
Estimated Expiration
2045-09-08

AI Technical Summary

Technical Problem

In existing sulfur autotrophic denitrification processes, sulfate ions generated by sulfur oxidation react with calcium ions dissolved from calcite to form slightly soluble calcium sulfate, which causes crystallization on the packing surface, forming a dense barrier that isolates the reaction interface. This results in short system stability and lifespan, as well as low alkali source utilization.

Method used

The porous composite particles contain sulfur matrix, calcium carbonate and magnesium oxide. Through the synergistic limitation of chemical composition and microphysical structure, the magnesium oxide preferentially reacts with acid to release magnesium ions and inhibits calcium sulfate crystallization. The internal porous structure allows nitrogen gas to be pulsed out to clean the mass transfer channel, and a viscoelastic valve body is formed by the bio-affinity hydrogel precursor to protect microorganisms.

Benefits of technology

It enables long-term maintenance of reaction interface renewal without relying on external intervention, avoids passivation, maintains system stability and denitrification efficiency, reduces operating costs, and improves alkali source utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121044713A_ABST
    Figure CN121044713A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water pollution treatment, and discloses a sulfur autotrophic denitrification filler for nitrogen wastewater treatment and a preparation method thereof.The sulfur autotrophic denitrification filler comprises composite particles capable of being degraded step by step, and the composite particles are synergistically limited by chemical compositions and microscopic physical structures; the main alkali source calcium-based carbonate and the sacrificial alkali source magnesium-based oxide establish an interface self-updating mechanism by utilizing the reaction rate difference; physically, a pore structure composed of a reaction chamber and a throat is built in the filler, self-cleaning of an endogenous mass transfer channel is achieved through denitrification product nitrogen, and through internal cooperation of chemical and physical mechanisms, the problems of interface passivation and pore silting self-locking of traditional sulfur-based filler caused by reaction products are solved; the active self-updating and long-term stable operation capabilities of the filler are realized, so that the application potential of a cheap alkali source is released.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a sulfur autotrophic denitrification packing material for treating nitrogen wastewater and its preparation method, belonging to the field of water pollution treatment technology. Background Technology

[0002] Currently, sulfur autotrophic denitrification is considered a cost-effective technology for treating high-concentration nitrate nitrogen wastewater because it does not require the addition of external organic carbon sources. In this process, the common practice is to physically mix sulfur particles, which act as electron donors, with inexpensive alkaline substances to neutralize the acid that is inevitably produced during denitrification. Among these, calcite, or limestone (CaCO3), has become a widely adopted alkaline source option due to its extremely low cost and huge reserves.

[0003] However, when this technical strategy moves from the laboratory to long-term large-scale engineering applications, a deep-seated operational paradox inherent in its core reaction mechanism begins to emerge: there is an irreconcilable contradiction between the long-term stability of the system and its economic feasibility. The reason is that the sulfate ions produced by sulfur oxidation react in situ with the calcium ions dissolved from calcite to generate slightly soluble calcium sulfate (CaSO4). This product directly deposits and crystallizes on the surface of calcite particles, gradually forming a dense physical barrier. This process is usually called armoring or interface passivation. As a result, although the amount of calcite inside the packing is still sufficient, its effective reaction interface has been completely isolated, causing its ability to neutralize acid to continuously decline until it is eventually lost. Consequently, the denitrification function of the entire system collapses due to acid-base imbalance.

[0004] To address this predicament, those skilled in the art have explored various approaches, but these attempts often encounter new technical or economic difficulties. For example, physical interventions such as periodic high-pressure water jetting or chemical cleaning are used to attempt to remove the passivation layer, but this undoubtedly increases the system's equipment complexity and operating energy consumption, contradicting the technology's original intention of low cost and low maintenance. Another approach is to completely abandon limestone and instead add highly soluble alkaline agents such as liquid alkali, but this negates its core cost advantage, rendering the choice of technical route meaningless. Specifically, existing technologies mainly suffer from the following problems: The shortcomings of this system are as follows: 1. The system has an inherent negative feedback self-locking mechanism, meaning that the continuous denitrification reaction generates passivation products that disrupt its operating conditions, resulting in a theoretical upper limit to the system's effective lifespan and operational stability; 2. The utilization efficiency of relatively inexpensive alkali sources is low. Due to surface passivation, most of the alkali source remains unused when the system fails, leading to a waste of resources and costs; 3. Existing technologies lack an intrinsic mechanism that can actively maintain the continuous renewal of the reaction interface from within the material, forcing the system to rely on expensive external intervention methods when facing passivation problems. Therefore, the technical problem to be solved by this invention is how to design a sulfur-autotrophic denitrification packing material that can avoid interface passivation and self-locking problems caused by reaction products through the intrinsic synergistic effect between material components without relying on external intervention, thereby achieving the long-term stable release of the full potential of inexpensive alkali sources. Summary of the Invention

[0005] This invention provides a sulfur autotrophic denitrification packing material for nitrogen wastewater treatment and its preparation method. Its main purpose is to solve the problems of unstable system operation, short lifespan and low alkali source utilization caused by the formation of a passivation layer on the surface of cheap alkali source by the reaction products of existing sulfur-based packing materials.

[0006] To achieve the above objectives, this invention provides a sulfur autotrophic denitrification packing material for treating nitrogen wastewater. The porous composite particles comprise a sulfur matrix as an electron donor, a calcium-based carbonate as the main alkali source, and a magnesium-based oxide as a sacrificial alkali source. The chemical composition and microstructure of the porous composite particles are synergistically defined as follows:

[0007] At the chemical composition level, in an aqueous solution at 25 degrees Celsius and pH 5.0, the apparent dissolution rate of magnesium oxide is higher than that of calcium carbonate. Magnesium oxide is configured to preferentially react with acid and thus release magnesium ions at the reaction interface of calcium carbonate.

[0008] At the microscopic physical structure level, the porous composite particles have a pore structure consisting of a reaction chamber and a throat connecting the reaction chamber to the outside of the particles. The pore structure is configured so that the nitrogen gas generated during the denitrification process accumulates pressure in the reaction chamber and is then pulsedly ejected through the throat, impacting the mass transfer channels inside the particles.

[0009] Preferably, the calcium carbonate is calcite and the magnesium oxide is lightly calcined magnesium oxide; the content of magnesium oxide is 5 to 35 parts by weight, based on 100 parts by weight of the sum of the weights of the calcium carbonate and magnesium oxide; and the mass ratio of the sulfur matrix to the total weight of the calcium carbonate and magnesium oxide is 0.8 to 1.6.

[0010] Preferably, the magnesium-based oxide is hard-burned magnesium oxide, which undergoes an exothermic hydration reaction when in contact with wastewater, resulting in a local temperature rise in the reaction micro-regions defined by the reaction chamber and throat inside the porous composite particles.

[0011] Preferably, the ratio of the equivalent diameter of the throat to the equivalent diameter of the reaction chamber is in the range of 0.05 to 0.30; wherein, the equivalent diameter of the throat is the diameter at the point where the cross-sectional area of ​​the throat is the largest, and the equivalent diameter of the reaction chamber is the diameter of the sphere equivalent to the volume of the reaction chamber; the interconnected porosity of the porous composite particles accounts for 20% to 45% of the total volume of the particles.

[0012] Preferably, the inner wall of the larynx is supported by a biocompatible hydrogel precursor, which together with the extracellular polymer secreted by denitrifying microorganisms forms a viscoelastic biovalve in the larynx. The viscoelastic biovalve undergoes viscoelastic deformation or overall displacement when the gas pressure in the reaction chamber increases.

[0013] Preferably, the biocompatible hydrogel precursor is an anionic polysaccharide, which is distributed at least at the surface pore inlet of the porous composite particles and fixes a predetermined type of toxic substance in the wastewater through ion chelation or chemical reaction, thereby reducing the concentration of the predetermined type of toxic substance in the wastewater entering the throat.

[0014] Preferably, the porous structure consisting of a reaction chamber and a throat is formed by removing a pore-forming agent pre-placed in the mixture during the granulation process. In a standard sulfate deposition test, the calcium sulfate coverage of the calcium carbonate surface of the porous composite particles is less than 30% after 48 hours. The conditions for the standard sulfate deposition test are: placing the porous composite particles in a static solution with a pH of 5.0 and a sulfate ion concentration of 2500 mg / L at 25 degrees Celsius.

[0015] Preferably, the porous composite particles are bonded together by an inert binder containing bentonite and dried and shaped at a temperature below 95 degrees Celsius; the amount of inert binder is 2% to 8% of the total weight of the porous composite particles.

[0016] Preferably, the anionic polysaccharide is sodium alginate or sodium carboxymethyl cellulose; the biocompatible hydrogel precursor is loaded onto the inner wall of the throat and the surface pore entrance of the porous composite particles through a two-stage impregnation coating process.

[0017] A method for preparing a sulfur autotrophic denitrification packing for nitrogen wastewater treatment includes the following steps:

[0018] Step a: The sulfur matrix, which serves as an electron donor, the calcium carbonate, which serves as the main alkali source, the magnesium oxide, which serves as the sacrificial alkali source, the inert binder, and the pore-forming agent are mixed to obtain a mixture.

[0019] Step b: Add water to the mixture and knead to form wet granules;

[0020] Step c: Dry the wet particles at a temperature below 95 degrees Celsius, and remove the pore-forming agent by dissolving or sublimation during the drying process or during the subsequent soaking process to form a porous structure consisting of reaction chambers and throats inside the particles, thereby obtaining dried particles;

[0021] Step d: When it is necessary to carry the bio-affinity hydrogel precursor, the dried particles are subjected to a second impregnation coating to carry the bio-affinity hydrogel precursor on the inner wall of the throat and at the pore entrance of the particle surface.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] 1. The filler of this invention establishes a self-regulating mechanism for the interfacial reaction environment by combining calcium carbonate, which serves as an electron donor and is the main alkali source, with a magnesium oxide that has a higher acid reaction rate than calcium carbonate. Under denitrification acid production conditions, the magnesium oxide reacts preferentially, and the ionic environment formed by its products can sustainably inhibit the crystallization and adhesion of the calcium sulfate hard shell on the surface of calcium carbonate. This allows the calcium carbonate reaction interface, which serves as the main alkali source, to be exposed and renewed for a long time, avoiding the problem of system kinetic decay and eventual failure caused by product passivation in traditional sulfur-based fillers.

[0024] 2. Based on the above mechanism, by selecting a specific hard-burned magnesium oxide as the magnesium-based oxide, a temperature compensation function is introduced into the system. While the hard-burned magnesium oxide undergoes a neutralization reaction upon contact with wastewater, its hydration releases heat. This heat directly acts on the reaction micro-zones inside the particles, which can locally increase the interface temperature of the core reactants when the external water temperature is low. This maintains the reaction rate of magnesium-based oxides and calcium-based carbonates with acids, ensuring that the core interface anti-passivation function and overall treatment performance of the packing remain stable under different seasonal and operating temperature fluctuations. Furthermore, the composite particles of this invention have a specific pore structure pre-set inside, consisting of a reaction chamber and throats connecting it to the particle surface. This structure ensures that the nitrogen gas generated during denitrification must first overcome the capillary resistance at the throat before escaping from the chamber, thus forming a brief pressure accumulation in the chamber and finally releasing it in a pulse form. This continuously distributed internal gas pulse can physically disturb the loosely attached biofilm fragments or inorganic particles on the inner wall of the pores, achieving long-term self-cleaning of the mass transfer channels inside the packing and extending the effective service life of the packing.

[0025] 3. The present invention further incorporates a biocompatible hydrogel precursor onto the inner wall of the throat. This precursor, in conjunction with extracellular polymers secreted by microorganisms, forms a viscoelastic biovalve within the throat. When the system encounters a high-load nitrogen shock that causes a sharp increase in internal gas pressure, the valve can dissipate the shock energy through its own viscoelastic deformation or overall displacement, thus providing a buffering and protective effect on the porous framework of the packing material. Simultaneously, if the hydrogel precursor, such as anionic polysaccharide, is also distributed at the pore inlet of the particle surface, it can preferentially fix certain specific toxic substances entering the wastewater through ion chelation or chemical reaction, providing a pre-isolated chemical environment guarantee for the stability of the internal core functional microbial community and the aforementioned valve structure, ultimately forming a stable operating system with both physical shock tolerance and chemical toxicity resistance. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the system operation process of the present invention;

[0027] Figure 2 This is a graph showing the relationship between the pore structure parameters and key performance indicators of the packing material of this invention.

[0028] Figure 3 This is a block diagram illustrating the internal synergistic mechanism of the packing material of the present invention;

[0029] Figure 4 This is a schematic diagram comparing the interface self-renewal mechanism of the filler of the present invention with the interface passivation phenomenon of traditional fillers. Detailed Implementation

[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0031] This invention provides a sulfur-based autotrophic denitrification packing material for nitrogen wastewater treatment and its preparation method. The packing material is a porous composite particle. During use, through the continuous reaction and consumption of the main alkali source and the sacrificial alkali source, the function is gradually released and the particles are simultaneously degraded. Through the synergistic limitation of chemical composition and microphysical structure, it aims to solve the problems of interface passivation and pore blockage caused by reaction products in existing sulfur-based packing materials, so as to achieve self-renewal and long-term stable operation of the packing material. The chemical composition of the packing material includes a sulfur matrix as an electron donor, a calcium carbonate as the main alkali source, and a magnesium oxide as a sacrificial alkali source. Its microphysical structure is provided with a pore network composed of reaction chambers and throats.

[0032] In the long-term operation of the sulfur autotrophic denitrification process, sulfate ions generated during sulfur oxidation react with calcium ions dissolved from the calcium carbonate, which serves as the alkali source, to form slightly soluble calcium sulfate, which deposits on the surface of the calcium carbonate particles, forming a dense physical barrier, i.e., interfacial passivation. This barrier prevents the calcium carbonate from contacting acidic wastewater, potentially leading to acid-base imbalance and reduced denitrification function. To address this issue, the porous composite particles of this invention feature a specific synergistic configuration at the chemical composition level, containing a sacrificial alkali source, magnesium oxide. In an aqueous solution at 25°C and pH 5.0, this magnesium oxide exhibits a higher apparent dissolution rate than the main alkali source, calcium carbonate. When the denitrification process begins to produce acid, the H+ in the microenvironment of the particle pores... + It preferentially reacts with magnesium-based oxides, and this preferential reaction releases a high concentration of magnesium ions (Mg) at the reaction interface of calcium-based carbonates. 2+ According to the principle of crystallization kinetics, the high concentration of coexisting cations increases the nucleation energy barrier of calcium sulfate and interferes with its regular lattice growth. At the same time, since the solubility of magnesium sulfate is much higher than that of calcium sulfate, the system will preferentially maintain the liquid phase of magnesium sulfate, thereby inhibiting the adhesion and crystallization of the solid phase calcium sulfate hard shell on the surface of calcium carbonate. This allows the effective reaction interface of calcium carbonate to be maintained and renewed for a long time. The effect was verified by a standard sulfate deposition test. That is, after placing the porous composite particles in a static solution with a pH of 5.0 and a sulfate ion concentration of 2500 mg / L for 48 hours at 25 degrees Celsius, the calcium sulfate coverage on the surface of calcium carbonate was less than 30%.

[0033] To achieve the aforementioned interface self-renewal mechanism, the types and proportions of each component were limited. Specifically, the calcium carbonate was calcite, and the magnesium oxide was lightly calcined magnesia. The content of the magnesium oxide was determined based on a total weight of 100 parts by weight for both calcium carbonate and magnesium oxide. The results showed that when its content was below 5 parts by weight, the released magnesium ion concentration was insufficient to form an effective crystallization-inhibiting environment at the calcium carbonate interface, and passivation still occurred. Conversely, when its content was above 35 parts by weight, excessive consumption of magnesium oxide led to premature particle formation. Excessive alkalinity release did not lead to further performance improvements but instead increased material costs. Therefore, the content of magnesium-based oxides was determined to be within the range of 5 to 35 parts by weight. Correspondingly, the mass ratio of the sulfur matrix (as an electron donor) to the total weight of calcium carbonate and magnesium-based oxides also has a suitable operating range. When this mass ratio is below 0.8, the sulfur matrix as an electron donor is insufficient, limiting the denitrification rate of the system. When this mass ratio is above 1.6, excessive sulfur matrix will generate acid exceeding the neutralization capacity of the alkali source, shortening the packing's lifespan. The effective lifespan was thus determined, and the mass ratio was set between 0.8 and 1.6. To further verify and calibrate the boundary effect of the mass ratio of sulfur matrix (as an electron donor) to total alkali source (the sum of the weights of calcium carbonate and magnesium oxide) on the long-term operating performance of the system, a verification experiment was conducted. Two experimental groups were set up: Group A had a sulfur-alkali mass ratio of 0.8, and Group B had a sulfur-alkali mass ratio of 1.6. After 90 days of continuous operation, it was observed that the pH value of the effluent from Group A (sulfur-alkali ratio 0.8) remained stable above 7.3 throughout the entire process, demonstrating excellent performance. The acid-base buffering capacity of the sample was different, but its average nitrate nitrogen removal rate remained stable in the range of 88% ± 3% in the later stage of operation. The reason is that the sulfur matrix, which is an electron donor, became the limiting substrate for the denitrification reaction. The experimental group B (sulfur-base ratio 1.6) maintained a nitrate nitrogen removal rate of more than 97% throughout the entire operation cycle, but its effluent pH value began to show a slow downward trend from day 55, and stabilized at 6.7 ± 0.1 at the end of the experiment. After the experiment, the packing was analyzed and it was found that the consumption of magnesium-based oxides inside it was significantly higher than that of the intermediate ratio group.

[0034] After solving the chemical-level interface passivation problem, the system still faces the physical-level progressive pore blockage problem during long-term operation. This means that detached, aged biofilm and inorganic particles slowly deposit in the mass transfer channels inside the packing material, leading to mass transfer obstruction and packing failure. In view of this, the porous composite particles of this invention are functionally designed at the microscopic physical structure level. They have an internal pore structure consisting of a reaction chamber and throats connecting the reaction chamber to the outside of the particles. This structure is formed by removing a pre-placed pore-forming agent from the mixture during granulation. The operating mechanism is as follows: nitrogen gas generated during denitrification first nucleates and accumulates in the relatively large reaction chamber. Due to surface tension, the gas must overcome the capillary resistance at the narrow throat when escaping, thus creating pressure buildup within the chamber. When the gas pressure inside the chamber is sufficient to overcome the capillary resistance at the throat, the accumulated gas is pulsed out through the throat. This continuous and distributed internal gas pulse can effectively remove loosely attached biofilm from the inner wall of the pores. Membrane fragments or inorganic particles generate physical disturbance and scouring, thereby achieving self-cleaning of the mass transfer channels inside the packing. Simultaneously, to ensure the effective realization of this internal gas pulse self-cleaning function, key geometric parameters of the pore structure were calibrated, namely the ratio of the equivalent diameter of the throat to the equivalent diameter of the reaction chamber. The equivalent diameter of the throat is the diameter at the point of maximum cross-sectional area, and the equivalent diameter of the reaction chamber is the diameter of the volumetric sphere equivalent to the reaction chamber. Experimental calibration revealed that when this ratio is below 0.05... If the throat is too narrow, the resistance to gas escape is too great, which may cause structural damage to the particles due to excessive pressure buildup. When the ratio is higher than 0.30, the throat is relatively wide, the capillary resistance is insufficient, and the gas cannot form effective pressure buildup and escapes directly. The pulse intensity is insufficient to achieve the sludge removal effect. Therefore, the ratio is determined to be in the range of 0.05 to 0.30. In order to ensure sufficient reaction interface and mass transfer channels, the interconnected porosity of the porous composite particles is set to account for 20% to 45% of the total particle volume.

[0035] Furthermore, when facing low-temperature wastewater conditions in winter, the decline in chemical reaction kinetics may weaken the reliability of the aforementioned interface anti-passivation mechanism. To address this situation, the present invention provides an implementation method with temperature compensation function, which uses hard-burned magnesium oxide instead of light-burned magnesium oxide as a sacrificial alkali source. When the hard-burned magnesium oxide comes into contact with wastewater, in addition to the neutralization reaction, it also undergoes a hydration exothermic reaction, namely MgO + H2O → Mg(OH)2 + Heat. This heat is directly released in the reaction micro-region defined by the reaction chamber and throat inside the particles. When the external water temperature is low, it can locally increase the temperature of the core reaction interface, thereby compensating for the decrease in reaction rate caused by low temperature. This allows the filler to maintain stable interface anti-passivation function and overall treatment performance under different operating temperature fluctuations.

[0036] Furthermore, conventional packing structures face challenges when the system encounters high-load nitrogen shocks or intermittent toxic substance shocks caused by accidental emissions from upstream. To address this, the present invention provides an implementation method with multiple shock resistance capabilities. This method utilizes a two-stage impregnation coating process to load biocompatible hydrogel precursors, such as sodium alginate or sodium carboxymethyl cellulose from anionic polysaccharides, onto the inner wall of the throat and at the pore inlets of the porous composite particles. These biocompatible hydrogel precursors, together with extracellular polymers secreted by denitrifying microorganisms, form a viscoelastic biovalve within the throat. Under normal operating conditions, this valve enhances gas pressure storage; however, under high-load nitrogen shocks causing internal... When the gas pressure increases, the valve body can dissipate the impact energy through its own viscoelastic deformation or overall displacement, thus providing a buffer protection for the porous skeleton of the packing. At the same time, the anionic polysaccharide coating distributed at the pore inlet of the particle surface can use the functional groups on its molecular chain to preferentially fix specific types of toxic substances in the wastewater, such as heavy metal cations or residual oxidants, through ion chelation or chemical reaction. This reduces the concentration of such toxic substances in the wastewater entering the throat, providing a pre-emptive chemical environment guarantee for the stability of the internal core functional microbial community and the valve body structure. Ultimately, this forms an operating system that combines physical impact resistance and chemical toxicity resistance.

[0037] The present invention discloses a method for preparing a sulfur autotrophic denitrification packing material for treating nitrogen wastewater, comprising the following steps: First, a sulfur matrix as an electron donor, a calcium carbonate as the main alkali source, a magnesium oxide as a sacrificial alkali source, an inert binder containing bentonite, and a pore-forming agent are mixed to obtain a mixture, wherein the amount of the inert binder accounts for 2% to 8% of the total weight of the porous composite particles; then, the mixture is kneaded with water to form wet particles; next, the wet particles are dried at a temperature below 95 degrees Celsius, and during the drying process or in a subsequent soaking process, the pore-forming agent is removed by dissolution or sublimation to form a porous structure consisting of reaction chambers and throats inside the particles to obtain dried particles; finally, when it is necessary to carry a biocompatible hydrogel precursor, the dried particles are subjected to a secondary impregnation coating to carry the biocompatible hydrogel precursor on the inner wall of the throat and at the pore inlet of the particle surface.

[0038] Example 1: This example is a specific application of the technical solution described in the foregoing specific implementation method in a specific industrial wastewater treatment scenario. In a chemical production facility that treats high-concentration nitrogen-containing wastewater, the discharged wastewater has the characteristics of nitrate nitrogen concentration higher than 400 mg / L, high sulfate concentration, and carbon-nitrogen ratio lower than 1.5. After the wastewater treatment system of this facility enters the winter operating condition, the influent temperature drops to below 10 degrees Celsius. After 90 days of operation, the pH value of the effluent of the autotrophic denitrification reactor using conventional sulfur and calcite mixed packing material continuously drops to below 5.5, and the denitrification efficiency drops from more than 95% initially to less than 30%. Eventually, the system fails. Upon inspection of the packing material, it was found that the surface of the calcite particles was covered with a dense layer of white calcium sulfate crystals, and the packing bed also showed signs of compaction.

[0039] To restore the function of the treatment system, the failed mixed packing was replaced with the porous composite particles of this invention. These particles were prepared according to the method of the specific embodiment, wherein the sacrificial alkali source was calcined magnesium oxide, and the particles were loaded with sodium alginate through a secondary impregnation coating process. After the system was restarted, under normal temperature conditions, the synergistic mechanism of the chemical composition inside the particles began to operate. The acid produced by denitrification preferentially reacted with the calcined magnesium oxide, which had a higher reaction rate. The magnesium ion microenvironment formed around the calcite reaction interface inhibited the crystallization and adhesion of calcium sulfate, allowing the surface of the calcite, which served as the main alkali source, to remain continuously exposed, thereby maintaining a stable pH environment and denitrification rate. When winter conditions arrived and the influent temperature dropped to 10 degrees Celsius, the calcined magnesium oxide underwent a hydration exothermic reaction, generating a local temperature rise in the micro-region defined by the reaction chamber and throat of the particles. This process compensated for the negative impact of the low temperature environment on chemical reaction kinetics and microbial activity, ensuring that the interface anti-passivation mechanism remained effective at low temperatures and preventing the system function failure previously caused by low temperatures.

[0040] After six months of stable system operation, a process fluctuation in the upstream production unit caused the nitrate nitrogen concentration in the wastewater entering the denitrification reactor to rise to 650 mg / L within 4 hours, accompanied by the infiltration of trace amounts of organic toxic substances. The sodium alginate coating on the pore inlet of the particle surface preferentially fixed most of the toxic substances entering the particle through ion chelation, providing a chemical environment protection for the internal microorganisms. Under the impact of high-concentration nitrate nitrogen, the activity of the protected microorganisms inside the particle increased, leading to a sharp increase in nitrogen production. The gas pressure formed in the reaction chamber was higher than under normal operating conditions. At this time, the viscoelastic biovalve formed by sodium alginate and extracellular polymers in the throat dissipated the impact energy of the rapid gas pulse through its own viscoelastic deformation and partial displacement, playing a role in buffering protection and safe pressure relief, preventing the particle structure from rupturing due to internal high pressure. At the same time... The nitrogen gas continuously generated during the denitrification process is released in pulses through the throat, periodically disturbing the biofilm debris and inorganic particles that slowly accumulate in the mass transfer channels inside the particles, maintaining the unobstructed pores. This physical self-cleaning effect and the chemical interface self-renewal effect work synergistically, with the former ensuring the effective transfer of reactants and products, and the latter ensuring the continuous progress of the chemical reaction. After a year of continuous operation, including a complete winter low-temperature cycle and several unplanned load shock events, the sulfur autotrophic denitrification system using the packing material of this invention maintained a stable effluent nitrate nitrogen concentration below the discharge standard. The system pH value was automatically maintained in the range of 6.8 to 7.5 without the need for external alkali addition. When some packing particles were taken out for testing, no obvious calcium sulfate hard shell layer was observed on the surface of the calcite inside, and the pore structure remained intact and unobstructed. The system achieved a stable operating cycle of more than one year.

[0041] Example 2: To quantitatively verify the stability and anti-passivation performance of the packing material of the present invention during long-term operation, an accelerated comparative test was established. The purpose of the test was to examine the differences in key performance indicators between the packing material of the present invention and conventional sulfur-based packing materials by simulating high-load conditions that easily lead to calcium sulfate crystallization. The test platform consisted of two parallel-operating upflow anaerobic packed bed reactors of the same specifications. The effective volume of each reactor was 2.0L. The reaction temperature was kept constant at 25.0 degrees Celsius by an external water bath jacket with a temperature control accuracy of ±0.5 degrees Celsius. The influent was supplied at a constant speed by a peristaltic pump with a flow rate setting accuracy of ±2%.

[0042] The experiment included a control group and an experimental group. The control group reactor was filled with conventional packing material consisting of a physical mixture of sulfur powder and calcite particles. The experimental group reactor was filled with the porous composite particles of the present invention, prepared according to a specific implementation method. The particle size range of both packing materials was 3.0 to 5.0 mm, and the weight ratio of sulfur matrix to total alkali source remained consistent. Artificially prepared simulated wastewater was used, and its water quality parameters were set to exert continuous pressure on the alkali source stability of the packing material, specifically including nitrate nitrogen. Concentration 400 mg / L, sulfate The concentration is 1500 mg / L, and trace elements such as phosphate, which are necessary to maintain microbial activity, are added. The hydraulic retention time (HRT) of the system is set at 6.0 h. This parameter is set to balance nitrate load and reaction sufficiency to ensure that the biological denitrification process is not limited by hydraulic conditions during the stable period, so that the chemical stability of the packing material itself becomes the main variable affecting the long-term performance of the system.

[0043] After inoculating activated sludge and undergoing a 15-day start-up and commissioning period, both reactors entered a 120-day continuous operation and monitoring phase. During the initial 30 days of operation, the performance of the two systems was similar, with effluent pH values ​​maintained above 7.3 and nitrate nitrogen removal rates exceeding 97%. From day 45 onwards, the performance of the control group began to deteriorate, with its effluent pH value dropping to 6.82, while the experimental group remained stable at 7.35. By day 60, this difference had widened further; the control group's effluent pH value had decreased to 6.41, and the corresponding nitrate nitrogen removal rate had also declined to 75.6%, while the experimental group's nitrate nitrogen removal rate had decreased significantly. The nitrate nitrogen removal rate remained at 97.5%. On the 90th day of the trial, the pH value of the effluent in the control group had dropped to 5.88, and the nitrate nitrogen removal rate was only 31.4%, indicating that its acid neutralization capacity and denitrification function had seriously declined. At the same time, the pH value of the effluent in the experimental group was still 7.25, and the nitrate nitrogen removal rate was as high as 96.8%. By the 120th day of the trial, the pH value of the control group had further dropped to 5.65, and the nitrate nitrogen removal rate was only 24.1%, while the pH value and nitrate nitrogen removal rate of the experimental group remained stable at 7.23 and 96.6%, respectively, demonstrating continuous operational stability.

[0044] The divergent trends in the above experimental data confirm the different internal mechanisms of the two packing materials. The performance degradation of the control group was due to the calcium sulfate armoring phenomenon on the calcite surface, which led to the gradual loss of its acid neutralization capacity. The reason why the experimental group was able to maintain long-term stable pH and denitrification performance is that the sacrificial alkali source magnesium oxide inside the particles preferentially reacts with acid, forming an ionic microenvironment that inhibits calcium sulfate crystallization at the interface of the main alkali source calcite, thus ensuring the long-term effectiveness of the main alkali source. After the experiment, the two packing materials were dissected and analyzed. It was also observed that the calcite particles in the control group had a dense white coating layer on their surface, while the calcite surface inside the particles in the experimental group remained basically clean. This comparative experiment proves that the porous composite particles of the present invention, through the synergistic effect of their internal chemical components, can avoid the interface passivation problem caused by reaction products while using calcium carbonate as the main alkali source, thereby achieving long-term stable operation of the sulfur autotrophic denitrification system under the condition of treating high-concentration nitrogen-containing and sulfate-containing wastewater.

[0045] Example 3: This example combines Figures 1 to 4 This paper describes the implementation of a sulfur-autotrophic denitrification packing material for nitrogen wastewater treatment and its preparation method. Figure 1 As shown, after high-nitrogen wastewater enters the reactor with denitrifying microorganisms, the composite packing acts as an electron donor to initiate the denitrification process. The acidic substances produced in this process simultaneously activate two major mechanisms: interface self-renewal and self-cleaning. The former activates interface protection and maintains alkalinity balance through preferential reaction of magnesium oxides, while the latter uses generated nitrogen gas for gas pulse cleaning to keep the mass transfer channels unobstructed. The synergistic effect of the two ensures the long-term stable operation of the system and produces consistently compliant effluent. The pH and denitrification rate of the treated effluent are monitored by the system monitoring section to provide feedback on the operating status and data support for continuous optimization.

[0046] like Figure 2 As shown, the horizontal axis represents the ratio of the equivalent diameter of the throat to the reaction chamber, ranging from 0.05 to 0.30, while the vertical axis represents the performance index. The three curves in the figure represent the relationship between the gas pulse intensity (relative value), the structural stability score, and the comprehensive performance index as a function of this ratio. As the ratio increases from 0.05 to 0.30, the gas pulse intensity continuously decreases, while the structural stability score increases accordingly. The comprehensive performance index, as a balance between the two, provides a quantitative basis for optimizing the selection of pore structure parameters within the ratio range defined by this invention.

[0047] like Figure 3 As shown, porous composite particles serve as the core of the system, achieving self-renewal and stable operation through chemical and physical synergy. In the chemically synergistic interfacial self-renewal mechanism, the sulfur matrix participates as an electron donor in denitrification to produce acid (H+). +The sacrificial alkali source, magnesium-based oxide, preferentially reacts and releases Mg. 2+ Ions, thereby inhibiting CaSO4 crystallization on the surface of the main alkali source calcium carbonate and avoiding interface passivation; in the physical synergistic mass transfer channel self-cleaning mechanism, the pre-set pore structure composed of reaction chamber and throat allows the denitrification product nitrogen gas (N2) to accumulate and be pressurized before being pulsed out, thereby self-cleaning the mass transfer channel.

[0048] like Figure 4 As shown in the figure, the left side illustrates the interfacial passivation phenomenon of traditional packing materials, where the reaction interface between the sulfur matrix (S) and calcium carbonate (CaCO3) is covered by a dense CaSO4 passivation layer, thus blocking the continued reaction. The right side illustrates the interfacial self-renewal mechanism of the packing material of this invention, where the presence of the sacrificial alkali source magnesium oxide (MgO) allows MgO to form in the reaction microenvironment. 2+ The ion cloud, through its crystallization inhibition effect, prevents the deposition of CaSO4 on the surface of calcium carbonate, thereby ensuring the continuous renewal of the active reaction interface.

[0049] Example 4: In a specific engineering application scenario, a sulfur autotrophic denitrification system needs to be designed for a newly built industrial facility. The nitrate nitrogen concentration of the wastewater to be treated is stable, but the sulfate concentration fluctuates within the range of 1500 mg / L to 3000 mg / L due to different upstream production batches. To ensure that the system can operate stably for a long time within the entire fluctuation range, a standardized engineering calibration procedure needs to be established to determine the applicable process parameters and chemical ratios of the porous composite particles of the present invention. The core is to solve two technical problems: first, how to obtain particles with a predetermined pore structure through the control of the preparation process; and second, how to determine the appropriate sacrificial alkali source content to cope with the high-concentration sulfate environment based on this structure.

[0050] To address the first technical challenge—the directional construction of the pore structure comprised of the reaction chamber and throat—soluble sodium chloride was used as the pore-forming material. The final pore geometry parameters were controlled by adjusting the particle size of the pore-forming agent and the material ratio during the granulation process. Specifically, two sets of experimental samples were prepared. Sample one used sodium chloride microcrystals with a particle size distribution of 100 to 150 micrometers as the pore-forming agent, while sample two used sodium chloride particles with a particle size distribution of 400 to 500 micrometers. The types and proportions of sulfur matrix, calcium carbonate, magnesium oxide, and inert binder were kept consistent in both sets of samples. During the water-addition kneading granulation step… By controlling the amount of water added and the kneading shear force, the density of the wet granules was adjusted. The granules were then dried at a temperature below 95 degrees Celsius, and the sodium chloride porogen was removed by elution. The pore structure of the two groups of dried granules was characterized using mercury intrusion porosimetry. The results showed that sample group one formed a pore structure with a throat equivalent diameter to reaction chamber equivalent diameter ratio of approximately 0.25, while sample group two formed a pore structure with this ratio of approximately 0.08. This confirms that the porogen particle size mainly determines the size of the reaction chamber, while the granulation process parameters affect the formation of the throat. Through the synergistic regulation of both, the pore structure parameters can be stabilized within the target range of 0.05 to 0.30.

[0051] To address the second technical issue—determining the appropriate content of the sacrificial alkali source—two groups of particles from the previous step, exhibiting a more significant throat confinement effect, were selected as the physical structure substrate. Based on this, four batches of test packing materials, numbered one to four, were prepared. These four batches of packing materials shared the same physical structure, with a fixed mass ratio of sulfur matrix to the total weight of calcium carbonate and magnesium oxide at 1.2. The only variable was the content of lightly calcined magnesium oxide, serving as the sacrificial alkali source, in the total alkali source (the sum of the weights of calcium carbonate and magnesium oxide), which were 5 parts by weight, 15 parts by weight, 25 parts by weight, and 35 parts by weight, respectively. The four batches of packing materials were placed in independent reactors and subjected to accelerated aging tests using simulated wastewater at 25 degrees Celsius. The pH of the simulated wastewater was kept constant at 5.0, and the sulfate ion concentration was set at 2500 mg / L. This was to continuously monitor the passivation resistance of each batch of packing materials, and a stable effluent pH below 6.0 was considered a criterion for functional failure of the packing material.

[0052] The test results showed that the first batch of packing material, i.e., the sample with a magnesium oxide content of 5 parts by weight, experienced a continuous decline in effluent pH and eventually failed after about 30 days of operation. This indicates that under this high sulfate stress, the low content of sacrificial alkali source was insufficient to provide long-term interface protection. The second and third batches of packing material, i.e., the samples with magnesium oxide contents of 15 and 25 parts by weight, respectively, maintained stable effluent pH values ​​and did not experience functional failure during a continuous operation period of more than 90 days. The fourth batch of packing material, i.e., the sample with a magnesium oxide content of 35 parts by weight, also showed long-term stability. However, analysis of its particles after the test revealed that the residual amount of magnesium oxide inside was higher than that of the second and third batches, indicating that the excessive addition caused a certain degree of material redundancy while meeting the requirements for passivation resistance. This calibration procedure confirms that for wastewater with sulfate concentrations up to 2500 mg / L, setting the content of sacrificial alkali source magnesium oxide in the range of 15 to 25 parts by weight can balance passivation resistance and material utilization.

[0053] Example 5: In specific applications, to enable porous composite particles to withstand high-load nitrogen shock and intermittent toxic substances, secondary functional coating is required. This process follows a standardized impregnation and quality control procedure. First, the prepared dried particles, i.e., particles without biocompatible hydrogel precursors, are immersed in a 1.5% by weight sodium alginate aqueous solution for 60 seconds. This immersion time is designed to allow the hydrogel precursor solution with a certain viscosity to preferentially wet and adhere to the outer surface of the particles and the surface pore entrances, rather than completely penetrating deep into the particles. After immersion, the particles are removed and excess liquid is drained from the surface. Then, they are dried at a low temperature of 60 degrees Celsius until constant weight is achieved, thereby loading the biocompatible hydrogel precursor onto the inner wall of the throat and the surface pore entrances of the particles.

[0054] To verify the functional consistency of each batch of coated particles, a pre-shipment quality control procedure is required. This procedure involves measuring the wetting gas back pressure of the particles. To perform this measurement, the sampled coated particles are completely wetted in water and packed into a test column with a gas distribution plate at the bottom. Nitrogen gas is then introduced from the bottom of the test column at a constant low flow rate (0.2 times the reactor bed volume per minute). A micromanometer with an accuracy of 0.01 kPa monitors the pressure change at the bottom of the test column, recording the maximum pressure value corresponding to the first penetration of the packing layer and escape in a pulse; this is the gas pulse back pressure. For a qualified batch, the measured gas pulse back pressure should fall within a predetermined range of 1.05 to 1.25 kPa. Values ​​below this range indicate insufficient coating or uneven distribution, failing to form an effective viscoelastic bio-valve. Values ​​above this range may lead to excessive pressure buildup, affecting the normal operation of the system.

[0055] Example 6: To apply the packing material of this invention to wastewater treatment with different characteristics, an offline optimization parameter-finding procedure needs to be established to determine suitable pore structure parameters for specific operational objective functions. Specifically, for wastewater with high solids content and low gas production rate, the objective is to maximize resistance to physical clogging, while for wastewater with high gas production rate, the objective is to maximize the long-term structural stability of the particles. The resistance to physical clogging is quantified by the change in hydraulic pressure difference in the reactor bed, while the long-term structural stability is evaluated by the microstructural integrity of the particles after operation. Based on the process parameter control method of this invention, two... The porous composite particles, with identical parameters except for pore structure, were used in batches. The ratio of the throat to the equivalent diameter of the reaction chamber in batch one was controlled at approximately 0.08, while that in batch two was controlled at approximately 0.25. Parallel comparative experiments were conducted for the two applications, with two identical packed bed reactors set up for each application. One reactor was filled with batch one particles, and the other with batch two particles. The reactors were continuously operated for 90 days using simulated wastewater that matched the water quality of the target application. During this process, the pressure difference between the two ends of the bed was periodically measured at a constant influent flow rate to monitor clogging.

[0056] In the tests targeting the first type of application—wastewater with high solids content and low gas production rate—the reactor filled with batch two particles (a particle ratio of 0.25) experienced a slow and continuous increase in bed pressure differential starting from day 40, reaching 1.8 times its initial value by day 90. This indicates that the gas pulse intensity was insufficient to effectively remove the continuously entering inorganic particles. In contrast, the reactor filled with batch one particles (a particle ratio of 0.08) maintained a stable bed pressure differential throughout the entire operating cycle, maximizing its resistance to physical clogging. In the tests targeting the second type of application—wastewater with high gas production rate—no significant changes were observed in the bed pressure differential of either reactor. However, when the microstructure of the particles was examined after the experiment, microcracks appeared in the internal pore walls of the particles in batch one, while the structure of the particles in batch two remained intact, thus maximizing the long-term structural stability of the particles. The experimental results of this offline optimization parameter-finding procedure established a set of selection criteria for pore structure parameters. Specifically, for wastewater with low gas production rate but high risk of physical blockage, a ratio of the throat to the equivalent diameter of the reaction chamber close to 0.05 should be selected to optimize its physical self-cleaning effect; while for wastewater with high gas production rate, a ratio close to 0.30 should be selected to optimize its long-term structural stability.

[0057] Example 7: This example aims to verify the specific impact of the endpoint parameter of the sulfur matrix to total alkali source mass ratio (0.8 to 1.6) on system performance. The experiment was conducted using three parallel-running upflow anaerobic packed bed reactors (R1, R2, R3). The device specifications and operating conditions (temperature 25.0℃, HRT 6.0h, simulated wastewater quality) were consistent with those in Example 2. All three reactors were filled with the porous composite particles prepared in this invention. The pore structure parameters, particle size, and internal alkali source ratio (magnesium oxides accounted for 20 parts by weight of the total alkali source) of the particles were the same. The only variable was the mass ratio of sulfur matrix to total alkali source (the sum of the weights of calcium carbonate and magnesium oxides). The ratio was 1.2 for reactor R1 (control group), 0.8 for reactor R2 (low ratio group), and 1.6 for reactor R3 (high ratio group). The experimental results were obtained by continuous monitoring of the three systems for 100 days after a 15-day start-up period.

[0058] Reactor R1 (sulfur-alkali ratio 1.2) exhibited consistently high performance, with its effluent pH value remaining stable between 7.2 and 7.4, and its nitrate nitrogen removal rate consistently exceeding 96%, consistent with the results of the experimental group in Example 2. Reactor R2 (sulfur-alkali ratio 0.8) maintained an effluent pH value above 7.4 throughout the process, without acid accumulation. Its nitrate nitrogen removal rate remained above 95% for the first 60 days of operation, but after the 60th day, due to the relative insufficiency of sulfur matrix, the removal rate slowly decreased and eventually stabilized at around 89%, indicating that the system's processing capacity was limited by the electron donor supply. Reactor R3 (sulfur-alkali ratio 1.6) maintained an extremely high nitrate nitrogen removal rate of 98% throughout the entire monitoring period. However, due to the excessive sulfur matrix leading to a high acid production rate, the system's alkali source consumption accelerated, and its effluent pH value slowly decreased from 7.2 from the 50th day, dropping to 6.65 by the 100th day. The comparative data in this embodiment clearly confirms that a mass ratio of 0.8 is the lower limit to ensure that the system achieves high denitrification efficiency, while a mass ratio of 1.6 is the upper limit to prevent the system from prematurely shortening its effective operating life due to excessive acid production. Therefore, the range of 0.8 to 1.6 is the optimized range for achieving efficient, stable, and long-term operation.

[0059] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.

Claims

1. A sulfur-autotrophic denitrification packing material for treating nitrogen wastewater, comprising porous composite particles containing a sulfur matrix as an electron donor, a calcium-based carbonate as the main alkali source, and a magnesium-based oxide as a sacrificial alkali source; characterized in that, The chemical composition and microstructure of the porous composite particles are synergistically constrained as follows: At the chemical composition level, in an aqueous solution at 25 degrees Celsius and pH 5.0, the apparent dissolution rate of magnesium oxide is higher than that of calcium carbonate. Magnesium oxide is configured to preferentially react with acid and thus release magnesium ions at the reaction interface of calcium carbonate. At the microscopic physical structure level, the porous composite particles have a pore structure consisting of a reaction chamber and a throat connecting the reaction chamber to the outside of the particles. The pore structure is configured so that the nitrogen gas generated during the denitrification process accumulates pressure in the reaction chamber and is then pulsedly ejected through the throat, impacting the mass transfer channels inside the particles.

2. The sulfur autotrophic denitrification packing material for nitrogen wastewater treatment according to claim 1, characterized in that, The calcium-based carbonate is calcite, and the magnesium-based oxide is lightly calcined magnesium oxide; the content of magnesium-based oxide is 5 to 35 parts by weight, based on 100 parts by weight of the total weight of calcium-based carbonate and magnesium-based oxide; the mass ratio of sulfur matrix to the total weight of calcium-based carbonate and magnesium-based oxide is 0.8 to 1.

6.

3. The sulfur autotrophic denitrification packing material for nitrogen wastewater treatment according to claim 1, characterized in that, The magnesium-based oxide is hard-burned magnesium oxide, which undergoes an exothermic hydration reaction when in contact with wastewater, resulting in a local temperature rise in the reaction micro-regions defined by the reaction chamber and throat inside the porous composite particles.

4. The sulfur autotrophic denitrification packing material for nitrogen wastewater treatment according to claim 1, characterized in that, The ratio of the equivalent diameter of the throat to the equivalent diameter of the reaction chamber is in the range of 0.05 to 0.30; wherein, the equivalent diameter of the throat is the diameter at the point where the cross-sectional area of ​​the throat is the largest, and the equivalent diameter of the reaction chamber is the diameter of the sphere equivalent to the volume of the reaction chamber; the interconnected porosity of the porous composite particles accounts for 20% to 45% of the total particle volume.

5. The sulfur autotrophic denitrification packing material for nitrogen wastewater treatment according to claim 1, characterized in that, The inner wall of the larynx is supported by a bio-affinity hydrogel precursor. This bio-affinity hydrogel precursor, together with the extracellular polymer secreted by denitrifying microorganisms, forms a viscoelastic biovalve in the larynx. This viscoelastic biovalve undergoes viscoelastic deformation or overall displacement when the gas pressure in the reaction chamber increases.

6. The sulfur autotrophic denitrification packing material for nitrogen wastewater treatment according to claim 5, characterized in that, The biocompatible hydrogel precursor is an anionic polysaccharide, which is distributed at least at the surface pore inlet of the porous composite particles and fixes predetermined types of toxic substances in the wastewater through ion chelation or chemical reaction.

7. The sulfur autotrophic denitrification packing material for nitrogen wastewater treatment according to claim 1, characterized in that, The porous structure, consisting of a reaction chamber and a throat, is formed by removing the pore-forming agent pre-placed in the mixture during the granulation process. In the standard sulfate deposition test, the calcium sulfate coverage of the calcium carbonate surface of the porous composite particles is less than 30% after 48 hours. The conditions for the standard sulfate deposition test are: placing the porous composite particles in a static solution with a pH of 5.0 and a sulfate ion concentration of 2500 mg / L at 25 degrees Celsius.

8. The sulfur autotrophic denitrification packing material for nitrogen wastewater treatment according to claim 1, characterized in that, The porous composite particles are bonded together by an inert binder containing bentonite and dried and shaped at a temperature below 95 degrees Celsius; the amount of inert binder is 2% to 8% of the total weight of the porous composite particles.

9. A sulfur autotrophic denitrification packing material for treating nitrogen wastewater according to claim 6, characterized in that, The anionic polysaccharide is sodium alginate or sodium carboxymethyl cellulose; the biocompatible hydrogel precursor is loaded onto the inner wall of the throat and the surface pore entrance of the porous composite particles through a two-stage impregnation coating process.

10. A method for preparing a sulfur autotrophic denitrification packing for nitrogen wastewater treatment, characterized in that, Includes the following steps: Step a: The sulfur matrix, which serves as an electron donor, the calcium carbonate, which serves as the main alkali source, the magnesium oxide, which serves as the sacrificial alkali source, the inert binder, and the pore-forming agent are mixed to obtain a mixture. Step b: Add water to the mixture and knead to form wet granules; Step c: Dry the wet particles at a temperature below 95 degrees Celsius, and remove the pore-forming agent by dissolving or sublimation during the drying process or during the subsequent soaking process to form a porous structure consisting of reaction chambers and throats inside the particles, thereby obtaining dried particles; Step d: When it is necessary to carry the bio-affinity hydrogel precursor, the dried particles are subjected to a second impregnation coating to carry the bio-affinity hydrogel precursor on the inner wall of the throat and at the pore entrance of the particle surface.

Citation Information

Patent Citations

  • Sulfur autotrophic denitrification nitrogen removal slow-release composite filler as well as preparation method and application thereof

    CN115925111A

  • Sulfur autotrophic filler as well as preparation method and application thereof

    CN116143281A

  • Anti-scaling autotrophic denitrification nitrogen removal filter material as well as preparation method and application thereof

    CN117509896A

  • Treatment method of wastewater containing nitrate nitrogen

    JP2006224087A

  • Porous inorganic particle, and composite filler, product using the same

    US20240207489A1

Cited By

  • Multi-parameter intelligent regulation and control method and system for industrial wastewater treatment

    CN121764272A